What are the economic concerns on environment? Mapping the research trends and frontiers on air pollution and health. Issue 1 (31st December 2022) - Xie, Jie; Zhu, Mingying
Abstract: There is a growing body of economic literature focusing on the negative health effect of air pollution. This paper performs a data-driven analysis of 844 economic publications on air pollution and health in the last three decades. We provide a novel way to visualize the research patterns and features, including the numerical analysis, collaboration network analysis at macro-meso-micro levels, keyword co-occurrence network analysis, and co-citation connection analysis. Additionally, the comparison with the topic dendrogram in environmental science is supplemented to seek the potential research direction. The results reveal that the entire field is now experiencing the rapid development. United States has not only published the largest number of articles, but has also established the most extensive collaborations with other countries. Besides, there have developed a couple of stable cooperative teams consisting of the leading authors. Research topics are gradually leaning toward the developing countries, and research contents are turning to psychological health. More types of air pollutants are worthy of analysis in the future.